1980
DOI: 10.1002/pol.1980.170180712
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐resistant polymers with thianthrene analog units. II . Aromatic polyamides

Abstract: A series of polyamides which contained thianthrene, phenoxatiin, and dibenzo‐p‐dioxin units was synthesized from tricyclic fused‐ring diamines and aromatic diacid chlorides by solution polycondensations at a low temperature. The amorphous polyisophthalamides were highly soluble in polar organic solvents, whereas some of the polyterephthalamides with a fair degree of crystallinity were insoluble. The solubility of the series of polyamides increased in the order of the dibenzo‐p‐dioxin‐containing polymers < phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Polydithiathianthrenes have been made in which the backbone of the polymer consists completely of thianthrene units 29. Numerous thianthrene and thianthrene tetraoxide containing polyimides30–33 and polyamides34, 35 have also been studied. This article reports the first demonstration of incorporating a thianthrene group into the backbone of poly(aryl ether)s. Furthermore, the thianthrene heterocycle is investigated as the activating group for S N Ar in forming the poly(aryl ether thianthrene)s.…”
Section: Introductionmentioning
confidence: 99%
“…Polydithiathianthrenes have been made in which the backbone of the polymer consists completely of thianthrene units 29. Numerous thianthrene and thianthrene tetraoxide containing polyimides30–33 and polyamides34, 35 have also been studied. This article reports the first demonstration of incorporating a thianthrene group into the backbone of poly(aryl ether)s. Furthermore, the thianthrene heterocycle is investigated as the activating group for S N Ar in forming the poly(aryl ether thianthrene)s.…”
Section: Introductionmentioning
confidence: 99%
“…Reacting thianthrene diamines with terephthalic and isophthalic acid chlorides at low-temperature in Nmethylpyrrolidinone (NMP) gave novel aramids. 27,33 X-Ray diffraction indicated that the polyterephthalamides had significant crystallinity, whereas the polyisophthalamides were amorphous. The amide functionality increased solubility compared to polyimides containing thianthrene, benzo-p-dioxin and diphenyl sulfide units.…”
Section: Thianthrene-containing Macromoleculesmentioning
confidence: 96%
“…27,28 Several examples include reactions of substituted bis(o-iodophenyl) disulfide with copper, 29 thermal cyclization of substituted 2-mercaptophenyl phenyl sulfide, 30 aprotic diazotization of substituted 2-(phenylthio)phenyl-2-aminophenyl sulfide, 31 and thermal elimination of nitrogen from substituted 1,2,3-benzothiadiazole. 32 The advantage of using these reactions is the possibility of controlling the position of substitution.…”
Section: Properties Of Thianthrenementioning
confidence: 99%
“…Polymers containing the thianthrene group have been prepared that exhibit good semiconducting properties for applications in light emitting diodes 16, 17. The nonplanar conformation of the thianthrene heterocycle has been shown to improve solubility and processability of many polyamides18, 19 and polyimides15, 20, 21 by hindering crystallinity in these materials and decreasing polymer chain packing. Numerous other thianthrene containing polybenzoxazoles,22 polyquinolines,23 and poly(aryl ether)s24 have also been prepared.…”
Section: Introductionmentioning
confidence: 99%